NMDA receptor encephalitis with cancer of unknown primary origin - Çoban, Arzu; Gündoğdu, Gökçen; Poyraz, Mürüvvet; Yeğen, Gülçin; Demirtaş-Tatlıdede, Aslı; Bilgiç, Başar; Hanağası, Haşmet; Tüzün, Erdem; Gürvit, Hakan (Wichtig Publishing, 2016)
Purpose: N-methyl-D-aspartate receptor (NMDAR) encephalitis may present as a paraneoplastic syndrome in young women and is often associated with ovarian teratoma. Methods: We report 2 male cases of NMDAR encephalitis presenting with metastatic cancer of unknown primary origin. Results: Both patients showed cognitive dysfunction as well as other neurological symptoms, slow waves on EEG, and NMDAR antibodies in sera and CSF. Symptoms were effectively treated by pulse steroid and intravenous immunoglobulin treatment. The patients developed metastatic small cell neuroendocrine carcinoma of the parotid gland and inguinal metastatic squamous cell cancer shortly after their neurological episodes. Follow-up PET studies showed small cell lung cancer in the first patient while no primary origin could be found in the second patient. Conlusions: Our cases imply that NMDAR encephalitis may present with metastatic cancers that display slow progression rates and occur after encephalitis attacks.
WOS: 000388282800002
PubMed ID: 26481863
Keywords: Autoimmune Encephalitis; Ion Channel Antibody; Metastatic Tumor; NMDA Receptor